(untitled) (Indian Journal of Animal Production and Management, 2014)
This study was undertaken to evaluate the efficacy of nutritional therapeutic management for induction of estrus in acyclic does in order to increase the kidding percentage at farmers flock. The results indicated that under field condition deworming with suitable antihelminthic, proper balance feeding, mineral supplement and vitamin AD3E injection can be effectively used for induction of estrus in goats in semi arid environment.